SMS MESSAGES IN A DAILY FINNISH NEWSPAPER. THE CONTEXT OF PROVERB PERFORMANCES SMS SPOROČILA V FINSKEM ČASOPISU. KONTEKST IZVEDB PREGOVOROV - Liisa Granbom-Herranen (Zalozba Z R C, 2022)
The article focuses on Finnish proverbs as a part of contemporary colloquial written language in everyday use and context. The article offers a view on what is happening with proverbs in the vernacular in Finnish everyday life. Most traditional Finnish proverbs originate from an agrarian context and still use agrarian language, even if nowadays they live in a new context with a new meaning. As empirical material this article uses a special case that demonstrates the use of proverbs in one Finnish newspaper: proverbs in SMS messages published as a letter to the editor in a newspaper.
***
Avtorica se osredinja na finske pregovore kot del sodobnega pogovornega pisnega jezika v vsakdanji rabi in kontekstu. Članek ponuja pogled na to, kaj se dogaja s pregovori v domačem jeziku v finskem vsakdanjiku. Večina tradicionalnih finskih pregovorov izvira iz agrarnega konteksta in še vedno uporablja ta jezik, čeprav gre danes za nove kontekste z novimi pomeni. Empirično gradivo za razpravo so pregovori v finskem časopisu, natančneje, pregovori v SMS sporočilih, objavljenih kot pisma uredniku časopisa.